Theme and rheme: The contribution of thematic progression to the cohesiveness of writing discussion texts - Rusdi Noor Rosa; T. Thyrhaya Zein; Isvanelly Anwar (Studies in English Language and Education, 2026)
Writing a discussion text presents a formidable challenge for university students as they grapple with diverse viewpoints, potentially impeding the attainment of cohesion. This paper aims to investigate the contributions of thematic progression to the cohesiveness of ideas within the discussion texts written by university students. Using a descriptive method, this study involved 35 third-year students from the English Department at Universitas Sumatera Utara as the participants. The data were collected using a writing test, during which the students were asked to write a discussion text consisting of between four and five paragraphs. The analysis was conducted using an interactive model of data analysis. The results of the study illuminate the prevalence of simple linear progression as the dominant thematic progression pattern in the students’ discussion texts, indicating their concerted efforts towards fostering cohesion. However, the frequent use of constant continuous theme progression suggests potential areas for improvement in the students’ texts. In conclusion, the thematic progression patterns employed in the students’ discussion texts underscore the criticality of judiciously selecting suitable thematic progressions to improve idea cohesion. This research sheds light on the imperative role of thematic progression in fortifying the cohesiveness of ideas within discussion texts, offering valuable insights for educators and learners alike.